Perlindungan Perempuan Dalam Pembagian Harta Gono Gini Sebagai Akibat Putusnya Perkawinan Akibat Perceraian - Seri Mughni Sulubara (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Joint property in other terms is also called gono-gini property which means joint property both movable property (motorbikes, cars, shares, etc.) and fixed property (land, houses, etc.) held during the marriage period Thus, gono-gini property after divorce must be divided equally between husband and wife, both in the nature of receivables and debts. Property in the form of a house by way of credit, the credit status also remains joint property which becomes gono-gini property. The form of legal protection that can be given to the ex-wife in the gono-gini property is that the judge can decide that the joint property that is on credit is sold through over credit to a third party, the proceeds of which are divided by one-half to the ex-wife and one-half to the ex-husband. In addition, the judge may decide that the remaining unpaid debt from the purchase of the joint credit property, namely one-half becomes the responsibility of the former husband and one-half becomes the responsibility of the former wife. The method used is a qualitative descriptive research method. The data collection technique or instrument used is library research by studying various books as literature, official documents, laws and regulations, results of previous research, and other literature sources related to the problems studied. The results showed that the legal protection given to ex-wives based on Article 32 paragraph (2) of Marriage Law Number: 1 of 1974, namely the house of residence (credit property), then the division of the property must be determined in court.